2017
DOI: 10.1007/s10584-017-1970-8
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs and values explain international differences in perception of solar radiation management: insights from a cross-country survey

Abstract: Solar radiation management (SRM) aims to counteract the negative consequences of global warming and is considered for deployment in the event that mitigation and adaptation efforts appear insufficient. However, because the potential ecological and political side effects of SRM are not well understood, and because SRM will cross national boundaries, an international research perspective on the general public's perception of this technology is required. We conducted an online survey on the general public's perce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
43
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 59 publications
(46 citation statements)
references
References 42 publications
3
43
0
Order By: Relevance
“…Only a few comparisons between countries have been made related to tampering with nature or related constructs (Bredahl, 2001; Dragojlovic & Einsiedel, 2013b; Gaskell et al., 2000; Macer, 1994; Macer et al., 1995; Visschers et al., 2017), and no clear or consistent pattern in the perception of tampering with nature between countries has been described.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Only a few comparisons between countries have been made related to tampering with nature or related constructs (Bredahl, 2001; Dragojlovic & Einsiedel, 2013b; Gaskell et al., 2000; Macer, 1994; Macer et al., 1995; Visschers et al., 2017), and no clear or consistent pattern in the perception of tampering with nature between countries has been described.…”
Section: Resultsmentioning
confidence: 99%
“…Tampering with nature was also measured by providing tampering with nature as a reason as to why one does not agree with a certain technology on a multiple‐choice scale ( n = 6) or by asking participants to indicate to which extent they believe that a technology is tampering with nature ( n = 4). Multiple articles measured specific tampering with nature directly with one or two items ( n = 9), for example, with the item, “Genetic testing is tampering with nature” (Henneman, Timmermans, & Van Der Wal, 2006), while other articles used three to nine items to measure specific tampering with nature ( n = 19) (Frewer et al., 2002; Gaskell et al., 2000; Ghasemi et al., 2013; Sjöberg, 2000b; Visschers et al., 2017). Thus, the operationalization of the specific measure of tampering with nature varies greatly between studies.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have demonstrated cultural factors for the variegated perceptions of emerging technologies (e.g., [47] for genetically modified food; [48] for nanotechnology; [49] for geoengineering) as well as digital technologies, particularly for robots [50,51]. One study [52] showed how, even among experts, religious views have an effect on the developmental pathways of robots and artificial intelligence in Japan and the United States, with the Japanese demonstrating a preference for humanoid robots over other forms of artificial intelligence (without a body).…”
Section: Japanese Perspectives In the Global Debatementioning
confidence: 99%